Organizational Management of the Arabic Language Program at Pondok Pesantren Darussalam Sumani: Implementation, Constraints, and Solutions - Srirehani, Melinda Dewi; Ramadhani, Nida Husnia; Habib, Ikhwanul; Arifa, Zakiyah; Ifawati, Nur Ilah; Rizqi, Hafizh (ALSYS, 2025)
This study addresses the limited scholarly attention given to the organizing function in the management of Arabic language programs at Islamic boarding schools, despite its critical role in enhancing students’ language proficiency. Focusing on Darussalam Sumani Solok Islamic Boarding School, the research aims to examine how organizational structures and practices contribute to the effectiveness of its Arabic language program. Employing a qualitative case study approach, the study involves purposively selected program organizers and students as participants. Data were gathered through in-depth interviews, direct observations, and document analysis, and were subsequently analyzed thematically. The findings indicate that the program is systematically organized through OSPPD, featuring structured task delegation and scheduled activities such as ilqā’ mufradāt, muḥādathah, muḥāḍarah, kitāb kuning, and art performances that collectively foster a bi’ah lughawīyah (Arabic-speaking environment). Despite these strengths, the program faces persistent challenges, including low student motivation, limited vocabulary acquisition, an unconducive learning environment, and the absence of exemplary teaching models. The study concludes that while the organizing function is moderately effective, it requires reinforcement through cultural strategies, intensive coaching, and broader stakeholder engagement to ensure program sustainability. These findings underscore the significance of structured management and a coherent curriculum in advancing Arabic language acquisition within Islamic boarding school contexts. Further research should expand to multiple institutions and incorporate mixed-methods designs to enhance generalizability and depth of understanding.